Da Vinci's cat : a novel - Murdock, Catherine Gilbert (Greenwillow Books, 2022)
Using a mysterious wardrobe that allows them to travel through time, two eleven-year-olds, Federico a boy from the Italian Renaissance and Bee a girl from present-day New Jersey, work together to prevent the bickering between two great artists from changing the future.